2010
DOI: 10.1124/dmd.110.032268
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A, but Not Tacrolimus, Shows Relevant Inhibition of Organic Anion-Transporting Protein 1B1-Mediated Transport of Atorvastatin

Abstract: ABSTRACT:The aim of this study was to investigate the potential of calcineurin inhibitors [cyclosporine A (CsA) and tacrolimus (Tac)] to inhibit cellular uptake of atorvastatin mediated by the liver-specific organic anion-transporting polypeptide 1B1 ( The IVIVE showed that clinically obtainable concentrations of CsA, but not Tac, inhibit OATP1B1 transport of atorvastatin. CsA inhibition ranged from 28 to 77% within a dosing interval, whereas it was less than 1% for Tac, considering free concentrations and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 43 publications
6
113
2
1
Order By: Relevance
“…Instead, we confirmed that OATP1B1 and OATP1B3 were the primary transporters involved in atorvastatin uptake in vivo. The importance of OATP1B1 in hepatic atorvastatin uptake has been emphasized in other studies (Pasanen et al, 2007;Amundsen et al, 2010), but our data suggest that OATP1B3 is almost as important. The relatively high contribution of OATP1B3 to the uptake of atorvastatin differs from other statins, such as simvastatin acid and pitavastatin (Hirano et al, 2004;Elsby et al, 2012).…”
Section: Discussioncontrasting
confidence: 33%
“…Instead, we confirmed that OATP1B1 and OATP1B3 were the primary transporters involved in atorvastatin uptake in vivo. The importance of OATP1B1 in hepatic atorvastatin uptake has been emphasized in other studies (Pasanen et al, 2007;Amundsen et al, 2010), but our data suggest that OATP1B3 is almost as important. The relatively high contribution of OATP1B3 to the uptake of atorvastatin differs from other statins, such as simvastatin acid and pitavastatin (Hirano et al, 2004;Elsby et al, 2012).…”
Section: Discussioncontrasting
confidence: 33%
“…With the assumption of competitive inhibition, the inhibition constant, K i was estimated by eq. 4 (Amundsen et al, 2010):…”
Section: Methodsmentioning
confidence: 99%
“…Effect (Amundsen et al, 2010;Shitara et al, 2013a , the cells were lysed with 0.5 ml of 0.1 N NaOH overnight at room temperature. The resulting cell lysate was neutralized with 50 ml of 1 N HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Amundsen et al also demonstrated that the apparent K i value of cyclosporine A for the uptake of atorvastatin after 1-h preincubation with cyclosporine A was 1/22 of that in its coincubation. 40) Thus, it should be noted that the K i value obtained from the conventional assay may be overestimated, which leads to the underestimation of DDI risks.…”
Section: Clinical Importance Of Oatp-mediated Drug-drug Interactionsmentioning
confidence: 99%